RESOLUSI KONFLIK AGAMA: PERSPEKTIF FILSAFAT PERENIAL - Ahmad Asroni (UIN Sunan Kalijaga Yogyakarta, 2020)
Abstract: This article offers religious conflict resolution in the perspective of perennial philosophy. Essentially, perennial philosophy provides spaces of respect for religious diversity and plurality. The inner dimension (esoteric) which becomes the point of orientation and foothold of this philosophy enables it to be an instrument to minimize and even reduce conflicts between religious believers. The esoteric dimension offered by perennial philosophy allows all religions to coalesce and unite. Perennial philosophy presupposes that there are many paths to achieving truth, but all of these paths ultimately lead to one point, namely God.